COMPUTERIZED STEREOTACTIC BRAIN BIOPSIES: AN EXPERIENCE OF 15 PATIENTS AT AYUB TEACHING HOSPITAL - Bhatti, Sajid Nazir; Ayub, Shahid; Aurangzeb, Ahsan; Haq, Anwar Ul; Jamil, M.; Ali, Johar; Ahmad, Ayesha; Kashif, M. (Journal of Ayub Medical College Abbottabad, 2005)
Background: Deep seated lesions of the brain cannot be approached by conventional neurosurgical approach stereotactic system offers minimally invasive and accurate approach to such lesions. This study was carried out with an objective to determine the safety, efficacy and diagnostic yield of stereotactic biopsies of brain lesions using BrownRoberts-Wells (BRW) system. Methods: This study was carried out in patients with intracranial lesions at Ayub teaching hospital Abbottabad from September 1999 to October 2003. Suitable patients with intra cranial lesions underwent computerized stereo tactic biopsy with BRW system. Tissue specimens were analyzed in histopathology department of the Ayub Medical College and results were obtained. Data was analyzed via computer software SPSS 8.0 version for windows. Results: Fifteen patients were selected for stereotactic brain biopsy. Age ranged from 15 years to 54 years. Among them 09 (60%) were male and 06 (40%) were female patients. Out come of the procedure was highly promising in terms of safety and positive diagnostic yield in 14 patients (93.3%), and histopathalogical validity of results (93.3%). Only one patient suffered mild neurological deficit (6.7%), one patient had inconclusive tissue diagnosis and invalid result (6.7%). biopsy proven lesion was astrocytoma in 04 patients (26.7%), anaplastic astrocytoma in 04 (26.7%), gliomatosis in 02 (13.3%), tuberculomas in 03 (20.0%), metastatic adenocarcinomas in 01 (6.7%) and lymphoma in 01(6.7%). Conclusions: We conclude that computerized stereotactic brain biopsy is safe and effective procedure with a high diagnostic yield at our center. Key words: Computerized stereotactic biopsy, brain, Brown-Roberts-Wells (BRW) system,